Being Able and Willing to Innovate: A Study of Family Firm Identity and New Product Output among Dutch Private Businesses - Berent-Braun, Marta M.; Flören, Roberto H.; den Ouden, Michelle M.C.M. (Senate Hall, 2018)
We investigate the influence of family firm identity on new product output and whether this relationship is mediated by the ability and willingness of firms to innovate. Research on innovation in the context of family firms is in the early stages, and the results in the extant literature are equivocal. Recently, an ability and willingness approach to studying firm innovativeness has been introduced in the family business literature, mainly to explain innovation management and behavior in firms with family involvement. Based on a quantitative study of 255 Dutch private firms surveyed in 2017, this paper tests the mediating effect of ability and willingness on the relationship between family firm identity and new product output. We find no evidence for either a direct or indirect relationship between family firm identity and new product output. Hence, our study does not support the common conjecture that family firms are less innovative than nonfamily firms. Keywords: family firm, innovation, ability and willingness
Keywords: family firm|innovation